Is Diversity in Agricultural Production Lindked to Dietary Diversity Among Nepalese Women? Findings from the PoSHAN Community Studies. - Fitch, Claire. (Tufts University. Tisch Library., 2017)
This poster assesses the extent to which high and low ADP were associated with adequate women's diet diversity scores in order to inform nutrition-sensative agricultural interventions.; Keywords: Nepal, PoSHAN, Women, Diet diversity, agricultural interventions, Johns Hopkins University.; NIL Presentations 2013-2015.